Diagnostic utility of cytospin in comparison to cell block in peritoneal and pleural fluid cytology - Liz Maria Joseph; Sheeja Sainulabdeen; Sujatha, Deepa; Sankar Sundaram (Asian Journal of Medical Sciences, 2022)
Background: Fluid cytology plays an important role in delineating benign from malignant effusions, tumor staging, and also in diagnosing recurrences. Various methods are used in cytology for the preparation of smears. As the accurate diagnosis of the fluids aids in clinical decisions, the method of preparation of cytology smears, it is very important. Cytospin preparation of smears is one of the methods which provide higher cellular yield with better preservation of cellular morphology and is less time consuming. On the other hand, cell block method gives superior architectural details and provides options for immunocytochemistry. Aims and Objectives: The aim of this study was to assess the diagnostic utility of cytospin in comparison to cell block method in peritoneal and pleural fluid cytology. The study is done to determine the sensitivity, specificity, predictive values, and diagnostic accuracy of cytospin preparations with cell block method which is considered as the gold standard. Materials and Methods: This was a diagnostic test evaluation study done at the Department of Pathology, Government Medical College, Kottayam. The sample size was 240 which included all pleural and peritoneal fluids received in our cytology laboratory during the study period. Cytospin prepared smears of peritoneal and pleural fluids were compared with the tissue sections prepared by cell block method, to evaluate the diagnostic utility of cytospin. Tissue sections prepared from the cell blocks of effusions were considered as the gold standard for comparison. Results: A diagnostic test evaluation of cytospin preparation was done with cell block preparations. The sensitivity of cytopsin preparations in pleural and peritoneal fluid cytology is 94%. The specificity of cytopsin preparations in pleural and peritoneal fluid cytology is 100%. The positive predictive value of cytopsin preparations in pleural and peritoneal fluid cytology is 100% and the negative predictive value of cytopsin preparations in pleural and peritoneal fluid cytology is 96.8%. Hence, accuracy of the test is 97.9%. Conclusion: There is only minimal statistical difference between the results obtained by the cytospin and cell block methods. Cytospin method is less time consuming along with the advantage of higher cellular yield. Hence, the incorporation of cytospin along with the cell block technique is beneficial for augmenting the results of effusion cytology.